STUDI ELASTISITAS TALI DARI BAN SEPEDA MOTOR BEKAS SEBAGAI BAHAN KONSTRUKSI BANGUNAN RUMAH TAHAN GEMPA - Frilisa Dliyaul Haya; Masturi Masturi; Ian Yulianti (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Elasticity analysis of straps cut from used motorcycle tires done for determine (1) deflection effect to wide pieces of used tires, (2) modulus elasticity of used motorcycle tires, (3) used motorcycle tires applications for construction materials building earthquake resistant houses. Testing was conducted by One Point Loading (OPL) or a single centralized load testing. Data collection was performed by measuring the deflection at loading 1-10 kg with independent variable widths pieces of used tires. Modulus of elasticity obtained from the equation deflection. Data were analyzed with descriptive methods - quantitative regression analysis. Modulus elasticity of used motorcycle tires compared with the modulus elasticity of the construction materials. concluded that the larger the width of pieces of used tires, which occurs the smaller deflection. The modulus elasticity of used motorcycle tires is 8727.976 MPa which indicates that the used motorcycle tires have good flexibility. Straps cut from used motorcycle tires can be used as a construction material in addition to the retaining wall as a building collapse caused by the earthquake.Keywords: Elasticity, used tires, earthquake resistant houses.